Mitochondrial-DNA nucleotides G4298A and T10010C as pathogenic mutations: the confirmation in two new cases - Crimi, Marco; Galbiati, Sara; Sciacco, Monica; Bordoni, Andreina; Natali, Maria Grazia; Raimondi, Monica; Bresolin, Nereo; Comi, Giacomo Pietro (Mitochondrion, 2004)
Mitochondrial encephalomyopathies are highly variable clinically and at the genetic level. In practice, when the mitochondrial DNA (mtDNA) of any mitochondrial-patient is sequenced, a very high number of variations are noted. The vast majority of these differences are simply polymorphisms, that is, non-pathologic, homoplasmic sequence variations; however, when a heteroplasmic variant is detected (co-existence of two different populations in the same tissue) this is clinically significant. We identified two different heteroplasmic mutations in the mtDNA of two subjects: G4298A in the tRNA(Ala) (Alanine) gene and T10010C in the tRNA(Gly) (Glycine), both of which have been reported previously. This work confirms the pathogenicity of these mutations and helps define the correlation between genotype and phenotype.